The impact of Jordanian natural zeolite and silica fume on concrete performance sustainability - Ata, Tamara Hussein Bani; Ibraheem, Asma Thamir (Edelweiss Applied Science and Technology, 2025)
This study evaluates the combined impact of Jordanian natural zeolite and silica fume as additional cementitious materials (SCMs) on concrete mixtures. A normal mix, special concrete with natural zeolite, and other concrete with zeolite and silica fumes were prepared, focusing on various cement replacement percentages. The research emphasizes sustainability through efficient energy use and environmental preservation. Concrete specimens were tested for tensile splitting, compressive, and flexural strengths at 7 and 28 days to evaluate mechanical properties. Additionally, the study assessed permeability (water absorption), durability (sulfate resistance), and carbon footprint reduction using environmental impact assessment (EIA) methods for better performance investigation. Results showed that a 10% cement replacement with natural zeolite significantly improved permeability and durability compared to the normal mix. In contrast, combining silica fume and zeolite in concrete adversely affected concrete strengths. Microstructural analysis using scanning electron microscopic images and X-ray diffraction analyzed mixture compositions with a significant reduction in microcracks. These results highlight the challenges of SCMs to improve concrete durability and strength in rigid pavement applications, presenting realistic paths for the development of sustainable infrastructure with high-performance concrete.